Empirical Support for Establishing Common Assumptions in Cost Research in Education. Issue 1 (2nd January 2022) - Shand, Robert; Bowden, A. Brooks
Abstract: The economic evaluation of educational policies and programs employing the ingredients method for cost, cost-effectiveness, or benefit-cost analysis is no exception to the critique that economic models require an untenable number of assumptions. Educational economists must make assumptions due to two sources of uncertainty: model uncertainty, as in the well-documented debate over the selection of the appropriate social discount rate to calculate present value and empirical uncertainty due to the infeasibility of gathering sufficiently detailed data on all resources. This paper highlights the frequency of empirical assumptions made in the education literature and proposes a set of harmonized assumptions to address empirical uncertainty that can be used to increase comparability of economic evaluation across programs and across studies. By building consensus on a set of reasonable, empirically derived assumptions that are selected so as to minimally distort the results of evaluations, differences in costs, cost effectiveness, and benefit-cost ratios can be more confidently ascribed to meaningful differences in resource use, program implementation, and program effectiveness, as opposed to differences in choices made by the analyst.